Developing a framework of economic model for building component lifecycle repair - Ali, N. B. M. (Trans Tech Publications, 2011)
Building component maintenance management is one of the most important issues in management of building lifecycle costs. Key to successful maintenance management is the ability to survey present condition and predict future condition for each component and facility present in a building. One of the methods is condition-based. This paper reflects on the condition index progress in repair system and maintenance of building facility by research in similar subjects and looks specifically at the use of condition index (CI) as a development tool. The result of research can be published as a guide to assist the development of programmers in field of economic models for optimization of repair cost of building component.